ROLE OF UTERINE ARTERY DOPPLER ULTRASOUND IN PREDICTING PREECLAMPSIA IN PRIMIGRAVIDA: Predictor of Pre-Eclampsia With Uterine Artery Doppler - Awan, Fareeha; Ullah, Hidayat; Ahmad, Mashkoor (Pakistan Armed Forces Medical Journal, 2016)
Objective: To find the accuracy of uterine artery diastolic notching during the second trimester of pregnancy in predicting pre-eclampsia in primigravida patients. Study Design: Descriptive cross sectional study. Place and Duration of Study: Armed Forces Institute of Radiology & Imaging (AFIRI) Rawalpindi; six months duration from 30 Nov 2012 to 31 May 2013. Material and Methods: This study included 199 primigravida women with singleton pregnancy having diastolic notch in uterine arteries between 20 to 23 weeks of gestation. All patients were examined by both grey scale and doppler ultrasonography. Uterine arteries were evaluated with doppler near the point where they crossed the external iliac arteries. The patient was included in study if the presence of diastolic notch was demonstrated. Clinical follow up in gynae & obs department continued throughout the pregnancy to see if they developed preeclampsia. The data were recorded on a previously prepared proforma and analyzed with SPSS 21. Results: The accuracy of uterine artery doppler ultrasound in identifying women who later developed preeclampsia was 48.24%. The frequency of pre-eclampsia with bilateral notch was significantly high in the primigravid of younger age as compare to the primigravid of the older group (p=0.001). The difference in frequency of developing pre-eclampsia with bilateral notch when compared among 20 to 21 week gestational age and 22 to 23 weeks gestational age was statistically insignificant. Conclusion: Uterine artery diastolic notching between 20 and 23 weeks of gestation is an important risk factor for developing pre-eclampsia. This doppler parameter should, therefore, be included in the risk evaluation for gestational hypertension.